The Mining History of Greece in School Textbooks: The Case of Lignite - Kyriaki Makri; Christos Roumpos; Apostolos Antoniadis (Materials Proceedings, 2021)
The geological education in Greece is essentially rooted in the second half of the 19th century, since 1836, when secondary education was established in Greece. Although geology is referred to in all educational programs, its field was not taught before 1880, due to the lack of competent teachers and suitable books. Geological education in Greece was established as a ”necessary” science at the end of the above century, during Greece’s opening phase of mining activity. In particular, the first attempt to exploit lignite deposits began in Aliveri (Evia) in 1873, but the intensive exploitation in Aliveri began after the First World War, reaching an annual production of 23,000 tons by the end of 1927. Respectively, lignite mining began in Ptolemais in the 1950s and Megalopolis in the 1960s. In the present paper, the correlation of the lignite mining activity in Greece for electricity generation with the content of geoscience textbooks is investigated since it is widely accepted that education is directly linked to economic development.